Scows and small boats navigating Squaw Rapids between Miles Canyon and Whitehorse Rapids on the Yukon River, Yukon Territory, 1898. - Hegg, Eric A., 1867-1948 (1898)
Caption on image: "Squaw Rapids between Miles Canyon and White Horse Rapids Copyright 1898"